SIKAP GURU SEKOLAH DASAR DI KOTA SEMARANG TERHADAP PERUBAHAN KURIKULUM - Syaefudin, Mohamad; Budisantoso, Heri Triluqman (Universitas Negeri Semarang, 2007)
The objectives of this research are as follows: First, to discover the attitude ofprimary school's teachers in Semarang towards the curriculum changes. Second, todiscover what the teachers think of the new curriculum. The subject of this curriculumis the state elementary school teachers in Semarang who have experienced differentcurriculum changes twice in 1994 and 2004 respectively. The research reveals thatteachers showed 2 attitudes towards curriculum changes: high openness (76%) andmedium openness (24%) out of 100 respondents. Basically, we can classify theteacher's suggestion into 8 groups. They are government policy, infrastructure,program dissemination, dissemination, training, administrative affairs, curriculumcontent, sampling, and education.Kata kunci: sikap guru, perubahan kurikulum